IMPLEMENTASI KEBIJAKAN KURIKULUM 2013 PADA GURU SMA DI KABUPATEN KEBUMEN - Sri Rahayu; Zuli Qodir (Journal of Governance and Public Policy, 2016)
The many problems of education in Indonesia makes its own ambiguity for the executors, where policy-makersthink only of quantity without quality. One example is the Curriculum 2013, which are in a hurry to implement it soas to make the policy implementers be confusion as to a delay in textbook for teachers and training is notmaximized. This study aims to determine how the curriculum policy implementation in 2013 at a high schoolteacher in Kebumen with the location of this research is SMA Negeri 1 Kutowinangun, SMA Negeri 1 and 2Kebumen and education departments and sports Kebumen. The results of this study using the theory of George C.Edward III which indicates that the variable communication on indicators trasmisi and clarity executed well, this isbecause the education department and sports in collaboration with LPMP activities directly in the form of training,workshops, discussions, and technical guidance to teachers and principals. While the indicators consistentcommunication can be said is not consistent, which in the implementation of Curriculum 2013 regulations alwayschanging so make the school confusi implement it. Then the variable resources with indicators of humanresources (staff) and non-human (infrastructure) can be said not optimal this is because there are manyteachers who find difficulty in implementing Curriculum 2013. Variable disposition or attitude of policyimplementation can be quite good, where in the implementation of the implementers are always ready andresponsible with what is being implemented. In addition the system has to be undertaken systematically and inaccordance with the rules of Curriculum 2013. The fourth variable is a bureaucratic structure with indicatorStandard Operating Procedure (SOP) this can be evidenced by the guidelines in the implementation of Curriculum2013, then a good cooperation between agencies physical education and high school party in Kebumen.